The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1021/ef010239g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Size of Asphaltene Solubility Fractions

Abstract: A fluorescence depolarization technique was used to determine the molecular size of asphaltene solubility fractions of a petroleum resid asphaltene. The molecular size was determined at different emission wavelengths for each solubility fraction. For each subfraction the range of molecular size was found to vary considerably. However, at a given emission wavelength, the molecular sizes for the different asphaltene solubility subfractions are very similar, that is the subfractions differ from each other by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 22 publications
(36 reference statements)
13
138
0
5
Order By: Relevance
“…For instance Small-Angle X-ray and Neutron Scattering (SAXS and SANS) experiments were generally performed at concentrations close to 10 g.L -1 for asphaltenes dissolved in model solvents 17,18,[48][49][50][51] . It was not until 1999, using techniques such as fluorescence depolarization technique [52][53][54][55][56] , fluorescence correlation spectroscopy [57][58][59] and mass spectrometry 60,61 that reliable results, accounting for the molecular aggregation at higher concentrations, became available. These results have shown that typical mean molecular weights of asphaltenes were ∼750 g.mol -1 with a factor of 2 in the width of the molecular weight distribution.…”
Section: Structurementioning
confidence: 99%
“…For instance Small-Angle X-ray and Neutron Scattering (SAXS and SANS) experiments were generally performed at concentrations close to 10 g.L -1 for asphaltenes dissolved in model solvents 17,18,[48][49][50][51] . It was not until 1999, using techniques such as fluorescence depolarization technique [52][53][54][55][56] , fluorescence correlation spectroscopy [57][58][59] and mass spectrometry 60,61 that reliable results, accounting for the molecular aggregation at higher concentrations, became available. These results have shown that typical mean molecular weights of asphaltenes were ∼750 g.mol -1 with a factor of 2 in the width of the molecular weight distribution.…”
Section: Structurementioning
confidence: 99%
“…Several different methods have been applied to determine the molecular mass of asphaltenes and/or their different aggregation states: vapour pressure osmometry [16], small-angle neutron and X-ray scattering (SANS and SAXS, see below), mass spectrometry [8][9][10][11][12][13][14][15][16], fluorescence depolarisation measurements [9,10], and NMR [17,18]. Mass results are different in regard to the concentration range and the measurement technique.…”
Section: Structural Information From Scattering Measurementsmentioning
confidence: 99%
“…Despite the small number and limited range of data, a regression analysis yields the following relationships: (19) [η] = 0.049M w 0.41 (20) A 2 = 0.0129M w -0.55 (21) As previously explained in Section 1, all these power law type relations could be related to mass fractal organisation of the aggregates. Comparison of relations (19,20,21) with Equations (9,16,10) large q values, is a very strong indication of the fractal nature of asphaltene aggregates. It can be concluded that asphaltene solutions in toluene are described as a polydispersion of solvated aggregates characterised by a fractal dimension close to 2.1.…”
Section: Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, hydrodynamic properties such as intrinsic viscosity [4,5], diffusion coefficient [3,[6][7][8][9][10][11], and interface or surface tension [12][13][14] are used to elucidate information about the shape and size of heavy oil molecule in solution. In recent years, with the fast development of computer technology, molecular simulation has been applied into characterizing the shape and size of heavy oil molecules [15,16].…”
Section: Introductionmentioning
confidence: 99%